Os grupos de comercialização de etanol na região centro-sul do Brasil: uma análise das governanças em rede no elo indústria-distribuição - Marques, Dalton Siqueira Pitta (Universidade Federal de São Carlos, 2011)
Ethanol as fuel has an important role in the brazilian energy matrix and, recently, it has played a leading role in worldwide discussions on fuels alternative to oil. In Brazil, the ethanol industry comes from a period of major changes, caused by the deregulation of this same industry in the end of the 1990 s. These changes caused an impact on the forms in which business transactions between ethanol manufacturers and ethanol distributors were made, and the period immediately after the deregulation was marked by price competition between these two agents, rendering a result which was extremely favorable to the distributors. One of the effects of this deregulation was the consolidation of the strategy adopted by the ethanol manufacturers, which involves the formation of trading groups. The horizontal association of the companies, with a certain level of articulation and shared use of services and information, provides evidence of the existence of networks for the governance of the transactions between the ethanol manufacturers and the fuel distributors. However, there are still some coordination problems, which may reduce the cohesion and the bargaining power of this industry in the transactions with the distributors. In this context, this thesis has the purpose of showing the forms of organization of the ethanol trading groups and their governance mechanisms built to improve their bargaining conditions with the distributors. In order to really analyze if trading groups are a network governance structure, this work will use the theoretical basis of Industrial Economics, Transaction Cost Economics and Networks. In this last item, this work will approach the concept of cohesion. As a research method, the author used qualitative and exploratory initial research, followed by a multiple case study, in which the relations between manufacturers, trading groups and distributors are studied. It was possible to conclude that trading groups characterize network governance in the transactions between ethanol manufacturers and distributors, which made possible for them to balance the power game between manufacturers and distributors. Groups with different legal constitutions and forms of organization result in a multifaceted governance. This also reflects on the relevant factors of the cohesion, which range from shared values and equivalent size of companies, in one group, to reputation and power of its members in the other group. Finally, it was possible to observe that, although there are opportunistic behaviors of some agents, which may harm this cohesion, most associates are committed to their groups, which is illustrated by the positive attitude of manufacturers and the desire to enhance the relationship.
Keywords: Engenharia de produção; Redes de empresas; Estruturas de governança; Setor sucroalcooleiro; Grupos de comercialização; Coesão; Network of companies; Governance of transactions; Sugar and ethanol industry; Trading groups; Cohesion; ENGENHARIAS::ENGENHARIA DE PRODUCAO